Kaskitamasowin miýw-āyāwin - Vanessa Van Bewer (York University Libraries, 2020)
The following is a poetic re-presentation of Madeline Dion Stout's (2012) editorial: Ascribed Health and Wellness, Atikowisi Miýw-āyāwin, to Achieved Health and Wellness, Kaskitamasowin Miýw-āyāwin: Shifting the Paradigm.